ISLAMISME, MODERASI BERAGAMA, DAN SOLO GENEOLOGI PEMAHAMAN MODERASI BERAGAMA KELOMPOK ISLAM DI SOLO - Warsito, W; Abdillah, Anisa; Fadhilah, Lulu'; Abdillah, Anaqoh (MAMBA'UL 'ULUM, 2024)
The diversity of beliefs, religions and cultures of the Indonesian nation is an inevitability that often causes friction between residents. Some groups force their beliefs on other groups and even commit violence in the name of religion to achieve this goal. This is what drives the government through the Ministry of Religion to promote Religious Moderation so that Indonesian people do not get caught up in religious fanaticism. This study is a library research that uses books and journals as the main documents with the background of the city of Solo which is known as one of the pockets of the Islamic movement. The study found that the extreme understanding of Islamic groups is based on their belief that Indonesia is not an Islamic country that must be Islamized and based on their understanding of wala' wal bara' which forms an understanding to be hostile to infidels and reject their leadership. Therefore, strengthening literacy and dialogue are the means that must be carried out to change this extreme understanding.